Monitoring of Intraperitoneal Fluid Volume during Peritoneal Equilibration Testing using Segmental Bioimpedance - Fansan Zhu; Samer R. Abbas; Roxana M. Bologa; Nathan W. Levin; Peter Kotanko (Karger Publishers, 2019)
Background: Ultrafiltration failure and fluid overload are common in peritoneal dialysis (PD) patients. Knowledge of intraperitoneal volume (IPV) and time to peak IPV during a dwell would permit improved PD prescription. This study aimed to utilize trunk segmental bioimpedance analysis (SBIA) to quasi-continuously monitor IPV (IPVSBIA) during the peritoneal dwell. Methods: IPVSBIA was measured every minute using lower-trunk SBIA (Hydra 4200; Xitron Technologies Inc., CA, USA) in 10 PD patients during a standard 240-min peritoneal equilibration test (PET). The known dialysate volume (2 L) rendered IPVSBIA calibration and calculation of instantaneous ultrafiltration volume (UFVSBIA) possible. UFVSBIA was defined as IPVSBIA - 2 L. Results: Based on dialysate-to-plasma creatinine ratio, 2 patients were high, 7 high-average, and 1 low-average transporters. Technically sound IPVSBIA measurements were obtained in 9 patients (age 59.0 ± 8.8 years, 7 females, 5 African Americans). Drained ultrafiltration volume (UFVdrain) was 0.47 ± 0.21 L and correlated (r = 0.74; p < 0.05) with end-dwell UFVSBIA (0.55 ± 0.17 L). Peak UFVSBIA was 1.04 ± 0.32 L, it was reached 177 ± 61 min into the dwell and exceeded end-dwell UFVSBIA by 0.49 ± 0.28 L (95% CI: 0.27-0.7) and UFVdrain by 0.52 ± 0.31 L (95% CI: 0.29-0.76), respectively. Conclusion: This pilot study demonstrates the feasibility of trunk segmental bioimpedance to quasi-continuously monitor IPVSBIA and identify the time to peak UFVSBIA during a standard PET. Such new insights into the dynamics of intraperitoneal fluid volume during the dwell may advance our understanding of the underlying transport physiology and eventually assist in improving PD treatment prescriptions.